Optimizing Granulocyte Colony-Stimulating Factor Transcript for Enhanced Expression in Escherichia coli - Datta, Sonal (Frontiers in Bioengineering and Biotechnology, 2021)
The human granulocyte colony-stimulating factor (G-CSF) is a hematopoietic growth factor used to prevent and treat neutropenia. G-CSF stimulates the bone marrow to produce infection-fighting granulocytes. Recombinant human G-CSF is produced in surrogate host Escherichia coli and is PEGylated at N-terminal. Considering the requirement of producing therapeutic G-CSF in large quantities, construct designing for high expression is critical for the biopharmaceutical and industrial application. Earlier studies have employed approaches such as codon optimization, use of strong promoters, employment of protein tags, secretion signals, optimization of protein folding, etc., for increasing expression and yield of therapeutic proteins. In this study, it was observed that mRNA transcribed from the native human cDNA of G-CSF and the codon-optimized variant leads to low protein expression in E. coli. To understand the underlying reasons, the mRNA secondary structure of the 5’ end of the G-CSF transcript was analyzed. This analysis revealed the presence of stable secondary structures at the 5' end of the G-CSF transcript, arising from the native human gene and even from the codon-optimized sequence. These secondary structures were disrupted through translationally silent mutations within the first 24 nucleotides of the transcript without affecting the protein sequence. Interestingly, through this approach, the G-CSF protein expression was increased 60 folds as compared to native G-CSF construct. We believe that these findings create a roadmap for optimization of G-CSF transcript for enhanced expression in Escherichia coli and could be employed to increase the expression of other therapeutic proteins.